Dabigatran Etexilate in the course of Electrical Cardioversion in Patients with Non-Valvular Atrial Fibrillation - N. A. Novikova; A. N. Volovchenko (Рациональная фармакотерапия в кардиологии, 2016)
Atrial fibrillation (AF) is the most common cardiac cause of systemic embolism and cardioembolic stroke. The risk of thromboembolic complications increases significantly when performing for electrical cardioversion. Vitamin K antagonists (warfarin) more often used to prepare for electrical cardioversion. However lately new oral anticoagulants (NOAC) are becoming more common for the prevention of thromboembolic events in patients with AF. Possibility to perform planned cardioversion while receiving dabigatran has been shown in a retrospective analysis of patients from the RE-LY study. The incidence of stroke and systemic embolism within 30 days after cardioversion was low and did not differ significantly in all groups. Thus, the results of the RE-LY study allow performing the planned and emergency cardioversion in patients receiving dabigatran. These results were later confirmed in other retrospective studies and meta-analyzes that are presented in this article. The X-VERT study and sub-analysis of the ARISTOTLE study showed the efficacy and safety of rivaroxaban and apixaban in preparation and performance of electrical cardioversion in patients with non-valvular AF. Long-term preparation courses for the cardioversion were used in the majority of patients in all published papers. By the present time a specially designed study directly aimed at assessing the NOAC effectiveness, in particular, dabigatran, in preparing and performing electrical cardioversion was not carried out in patients with AF. Some questions about the safety and efficacy of dabigatran during short preparation courses before electrical cardioversion remain.